Long‐term survival following fungal catheter‐related bloodstream infection for patients with intestinal failure receiving home parenteral support. Issue 1 (9th October 2022) - Bond, Ashley; Kopczynska, Maja; Conley, Thomas; Teubner, Antje; Taylor, Michael; Abraham, Arun; Pironi, Loris; Lal, Simon
Abstract: Background: A fungal‐related catheter‐related bloodstream infection (CRBSI) is less frequent than those induced by bacteria. In the past, a single episode of fungal CRBSI has been used as a marker of home parenteral nutrition (HPN) failure and thus a possible indication for intestinal transplantation. Methods: Survival outcomes were assessed from a prospectively maintained database of patients initiated on HPN for underlying chronic intestinal failure between 1993 and 2018, with a censoring date of December 31, 2020. Cox regression was performed to assess predictors of mortality with univariable and multivariable analysis. Results: A total of 1008 patients were included in the study, with a total of 1 364 595 catheter days. There were 513 CRBSI events recorded in 262 patients, equating to a CRBSI rate of 0.38/1000 catheter days. A total of 38/262 (14.5%) patients had at least one episode of fungal CRBSI, whereas 216/262 (82.4%) had at least one bacterial but no fungal CRBSI. The median time between HPN initiation and the first CRBSI episode was 20.6 months (95% confidence interval, 16.5–24.1). Episodes of fungal or bacterial CRBSI and the number of CRBSI episodes were not associated with increased mortality. Overall, 15 CRBSI‐related deaths were observed in the observation period (0.01 CRBSI deaths/1000 catheter days), two of these were fungal in origin. Conclusion: The occurrence of a fungal CRBSI does not increase the risk of death compared with patients who have bacterial CRBSI or those without a CRBSI event.